Una prueba simple para regresiones espurias - Antonio E. Noriega; Daniel Ventosa-Santaulària (Banco de México, 2011)
– It has been found that the t-statistic for testing the null of no relationship between two independent variables diverges asymptotically under a wide variety of nonstationary data generating processes. This paper introduces a simple method which guarantees convergence of this t-statistic to a pivotal limit distribution, when there are drifts in the integrated processes generating the data, thus allowing asymptotic inference. This method can be used to distinguish a genuine relationship from a spurious one among integrated (I(1) and I(2)) processes. Simulation experiments show that the test has good properties in small samples. When applying the proposed procedure to real data (including the marriages and mortality data of Yule), we do not find (spurious) significant relationships between the variables.
Keywords: C12; C15; C22; C46; 330; Spurious Regression; Integrated Process; Detrending; Asymptotic Theory; Cointegration; Monte Carlo Experiments